Capable or Incapable? Disability and Justification in Martha Nussbaum’s Capabilities Approach - Buttrey, Michael (Religious Studies and Theology, 2020)
This article evaluates Martha Nussbaum’s capabilities approach for its treatment of disability and philosophical grounding. A summary of Nussbaum’s claims on how her theory includes people with disabilities is followed by Eva Kittay’s demonstration that in Nussbaum’s approach exclusion results from the ambiguous role of human dignity. The argument then shows that Jean Porter’s appeals to virtue and human nature provide stronger philosophical grounding for making judgments about human flourishing than Nussbaum’s non-metaphysical liberalism, insufficient to account for her theory of capabilities. While Porter’s account of human nature does not escape Shane Clifton and Hans Reinders’ concerns about the exclusion of people with disabilities from the human ideal, her and John Berkman’s recovery of Thomistic ideas of infused virtue and grace do provide a more inclusive concept of the human telos.